Cell‐Free Extracts from Human Fat Tissue with a Hyaluronan‐Based Hydrogel Attenuate Inflammation in a Spinal Cord Injury Model through M2 Microglia/Microphage Polarization - Xu, Guang‐Yu; Xu, Shun; Zhang, Yu‐Xuan; Yu, Zi‐You; Zou, Fei; Ma, Xiao‐Sheng; Xia, Xin‐Lei; Zhang, Wen‐Jie; Jiang, Jian‐Yuan; Song, Jian (Small (Weinheim an der Bergstrasse, Germany), 2022)
Treatment for spinal cord injuries (SCIs) is often ineffective because SCIs result in a loss of nerve tissue, glial scar formation, local ischemia and secondary inflammation. The current promising strategy for SCI is the combination of bioactive materials and cytokines. Bioactive materials support the injured spinal cord, stabilize the morphology, and avoid excessive inflammatory responses. Fat extract (FE) is a cell‐free liquid component containing a variety of cytokines extracted from human fat tissue using mechanical methods. In this research, a biocompatible HAMC (hyaluronan and methylcellulose) loaded with FE is used to treat a model of spinal cord contusion in mice. The composite not only inhibits death of neuro‐ and vascular cells and leads to the preservation of neural and vascular structure, but also modulates the inflammatory phenotype of macrophages in the locally injured region. Specifically, FE promotes the polarization of macrophages from an inflammatory M1 phenotype to an anti‐inflammatory M2 phenotype. During the screening of the involved pathways, it is corroborated that activation of the STAT6/Arg‐1 signaling pathway is involved in macrophage M2 polarization. In summary, FE is a promising treatment for SCI, as it is easy to obtain, nonimmunogenic, and effective. Fat extract (FE) is a cell‐free liquid component containing a variety of cytokines extracted from human fat tissue using mechanical methods. In this research, a biocompatible HAMC (hyaluronan and methylcellulose) loaded with FE is used to treat a model of spinal cord contusion in mice, which demonstrate an impressing recovery.